Public dance halls, their regulation and place in the recreation of adolescents - Gardner, Ella, 1893-1942.; United States. Children's Bureau (Washington, U.S. Govt. Print. Off., 1929)
This pamphlet discusses the legislative regulation of public dance halls in twenty-eight states. Some of the regulations undertaken by the states include restrictions on attendance, hours of operation, supervision, and regulation of the physical and social conditions of the hall. The author also discusses some of the regulations and ordinances of 100 cities including one from Lincoln, Nebraska that required patrons to keep their bodies at least six inches apart.
At head of title: U.S. Department of Labor. Children's Bureau.
"Dance-hall legislation of 1926, 1927, and 1928": p. 56-57.
"List of references on dance halls": p. 54-55.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance; Dance halls -- Law and legislation -- United States; Amusements -- Law and legislation -- United States; Dance Ordinances and Regulations